Applicability audit committee on detecting financial statement fraud using diamond theory - Zea Riza Sinensis; Fuad (Jurnal Akademi Akuntansi, 2024)
Purpose: This study investigates the application of fraud diamond theory in the detection of financial statement fraud, utilizing financial targets, industry characteristics, auditor changes, and director changes as independent variables. Methodology/approach: This research focusing on healthcare companies listed on the Indonesia Stock Exchange (IDX) from 2016 until 2023, the study analyzes data from 32 firms, resulting in 185 analytical units. Employing panel data regression analysis through Eviews 12. Findings: The findings reveal that only financial targets show a positive and significant influence on financial statement fraud. In contrast, the other variables—industry characteristics, auditor changes, and director changes—show no significant impact. Additionally, while the audit committee moderates the relationship between industry characteristics and financial statement fraud, it does not influence the relationships involving financial targets, auditor changes, or director changes. Practical and Theoretical contribution/Originality: The novelty of this research is using the audit committee as a moderating variable to minimize the occurrence of financial statement fraud. Research Limitation: Future research is expected to use new theories, other proxies, and use different sector samples because this research is only limited to healthcare companies.